2014
DOI: 10.4049/jimmunol.1300261
|View full text |Cite
|
Sign up to set email alerts
|

IgA Enhances NETosis and Release of Neutrophil Extracellular Traps by Polymorphonuclear Cells via Fcα Receptor I

Abstract: Polymorphonuclear cells (neutrophils) are the first cells that arrive at sites of infections. According to the current dogma, they are involved in eliminating bacteria, after which they die through apoptosis. We now demonstrate that enhanced IgA-induced phagocytosis of bacteria or beads by neutrophils led to increased cell death. Nuclear changes and positivity for the general cell death marker 7-aminoactinomycin D were observed, but the absence of annexin V membrane staining supported that neutrophils did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 55 publications
3
101
0
3
Order By: Relevance
“…Furthermore, we showed that this nonapoptotic form of cell death, in the absence of bacteria, does not induce proinflammatory responses; rather, it promotes an anti-inflammatory cytokine microenvironment in coculture with macrophages. In the presence of bacteria, NETosis induced by IgA-opsonized particles appears to enhance immune defense (21). Conversely, our data suggest that, in the absence or following elimination of bacteria, the enhanced susceptibility of activated neutrophils to anti-inflammatory death induced by endogenous IgA or by FcaRI-targeting agents may accelerate the resolution of inflammation, even under antiapoptotic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, we showed that this nonapoptotic form of cell death, in the absence of bacteria, does not induce proinflammatory responses; rather, it promotes an anti-inflammatory cytokine microenvironment in coculture with macrophages. In the presence of bacteria, NETosis induced by IgA-opsonized particles appears to enhance immune defense (21). Conversely, our data suggest that, in the absence or following elimination of bacteria, the enhanced susceptibility of activated neutrophils to anti-inflammatory death induced by endogenous IgA or by FcaRI-targeting agents may accelerate the resolution of inflammation, even under antiapoptotic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Aleyd et al (21) recently reported that phagocytosis of IgAopsonized bacteria resulted in neutrophil ROS production, release of DNA NETs, and subsequent neutrophil death by a nonapoptotic form of death (NETosis). In a scenario in which pathogens are still present, the induction of NETosis by IgA-opsonized bacteria might prevent counterproductive anti-inflammatory signals in macrophages by other forms of cell death, including apoptosis (21). In contrast, subsequent to pathogen elimination, clearance of activated neutrophils by apoptosis, or another anti-inflammatory form of cell death, is essential to prevent excessive inflammation and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of neutrophils by IgA-immune complexes, however, induces multiple proinflammatory functions, including phagocytosis, antibodydependent cellular cytotoxicity (ADCC), degranulation, release of cytokines and chemokines, production of reactive oxygen species (ROS) and the release of NETs (Fig. 1b) [4,7]. Previously, our group showed that FcaRI triggering leads to the release of the chemoattractant leukotriene B4 (LTB4), thereby inducing neutrophil migration and recruitment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Immune components such as IgA, an important mucosal antibody, also trigger NET formation, which has been attributed to ROS production when opsonised particles are engulfed (Aleyd et al, 2014). Complement C5a in conjunction with cytokines, such as Interferon Alpha (IFN-) or Granulocyte-macrophage colonystimulating factor (GM-CSF), may also activate NETs, though these NETs are of a mitochondrial DNA source (Yousefi et al, 2009) PAMPs exist for identifying DNA, RNA, fungi, protozoa and cancer proteins.…”
Section: Pathogen Activation Of Nets Has Identified a Range Of Stimulmentioning
confidence: 99%